2017
DOI: 10.17977/um030v5i32017p099
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students Reading Comprehension Ability Through Integrated Thematic Learning With School Literacy Movement Support

Abstract: PISA's findings reported that Indonesian elementary school students (IESS) achieved their average reading comprehension ability which were below the standard set by OECD. This research proposed school literacy movement (SLM) as an apparatus to cultivate IESS reading and writing skill habit. SLM served as the basis for achieving the 2013 Curriculum requirement. This study applied quasi-experimental method with employed sample of 126 IESS of 5th and 4th graders and their teachers serving in four schools. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Elementary School, Makassar City. This can be seen from the difference in reading ability of students in Gunung Sari I Elementary School in Rappocini District, Makassar City before and after the implementation of GLS (reading activities 15 minutes before learning) which increases.On the other hand, Puspita, et all. (2017) in the study found that it has a significant influence to improve reading comprehension of 5th grade students in class after applying GLS on ITL learning that is able to overcome the literacy gap that exists among students due to diversity in backgrounds.Meanwhile, a research of Yulianto (2017) found that in the process of implementing School Literacy Movement (SLM), the school preparation phase has been implemented.…”
Section: Discussionmentioning
confidence: 96%
“…Elementary School, Makassar City. This can be seen from the difference in reading ability of students in Gunung Sari I Elementary School in Rappocini District, Makassar City before and after the implementation of GLS (reading activities 15 minutes before learning) which increases.On the other hand, Puspita, et all. (2017) in the study found that it has a significant influence to improve reading comprehension of 5th grade students in class after applying GLS on ITL learning that is able to overcome the literacy gap that exists among students due to diversity in backgrounds.Meanwhile, a research of Yulianto (2017) found that in the process of implementing School Literacy Movement (SLM), the school preparation phase has been implemented.…”
Section: Discussionmentioning
confidence: 96%
“…The effectiveness test of interactive e-module shows the improvement of students' learning outcomes in terms of knowledge, skill, and attitude, such as honesty, piety, hard work,-responsibility, discipline, independence, communication, curiosity, collaboration,-and caring for the environment [35]- [40]. Integrated learning can improve the competence of students [41]- [45].…”
Section: E Discussionmentioning
confidence: 99%
“…On the other hand, Puspita, et al (2017) conducted a study aimed at examining the effect of integrated thematic learning as a means of improving the reading ability of grade 5 elementary school students. Their research used the SLM program as a means of developing the reading and writing habits of elementary school students.…”
Section: Introductionmentioning
confidence: 99%